Ultrasonic Enhancement of Chondrogenesis in Mesenchymal Stem Cells by Bolt-Clamped Langevin Transducers - Jinhyuk Kim; Hyuncheol Bae; Hyuk-Soo Han; Jungwoo Lee (Micromachines, 2023)
We recently investigated the design and fabrication of Langevin-type transducers for therapeutic ultrasound. Effect of ultrasonic energy arising from the transducer on biological tissue was examined. In this study, the transducer was set to radiate acoustic energy to mesenchymal stem cells (MSCs) for inducing differentiation into cartilage tissue. The average chondrogenic ratio in area was 20.82% in the control group, for which no external stimulation was given. Shear stress was applied to MSCs as the contrast group, which resulted in 42.66% on average with a 25.92% minimum rate; acoustic pressure from the flat tip causing transient cavitation enhanced chondrogenesis up to 52.96%. For the round tip excited by 20 Vpp, the maximum differentiation value of 69.43% was found, since it delivered relatively high acoustic pressure to MSCs. Hence, the results from this study indicate that ultrasound pressure at the kPa level can enhance MSC chondrogenesis compared to the tens of kHz range by Langevin transducers.